Case report: A novel model for educating radiation therapists in small countries: Case study of the "Train the Trainer" initiative in Israel. (December 2018) - Katzman, Tamar; Symon, Zvi; Shelly, Esti; Luxenburg, Osnat
Abstract: Introduction: Israel, as a small country faces many challenges to deliver quality RTT education. As technologies evolve, the need for RTT education becomes acute. This resulted in the Ministry of Health, IAEA and ESTRO running the train the trainers (TTT) program in a unique format. Method: An expanded TTT program was run in Israel. This resulted in the establishment of the National Center for Radiotherapy Education (NCRE). Key elements of the NCRE include national leadership, high-tech teaching environment, simulation based teaching methodologies, and evidence based education. Educational outcomes of the RTT course run in the NCRE were measured and statistically analysed. Results: The measurement of educational outcome was highly significant ( p < 0.00001). The feedback from the course was very positive, with a high aggregate data mean score for all questions pertaining to the effect the course has on work, and efficient use of time. Discussion: The success of the RTT course of the NCRE is evident from the results. The impact of the TTT program went beyond RTT education, as the NRCE is a national radiotherapy education resource, utilized by all radiotherapy professionals. Conclusion: More knowledgeable RTTs may be able to work in advanced roles, taking on tasks from other sectors in the department; this could improve the efficiency of patient care and improve the safety of radiotherapy delivery.